ANALISIS KEPUASAN WISATAWAN MANCANEGARA TERHADAP TOURIST INFORMATION CENTRE DI LABUAN BAJO, NUSA TENGGARA TIMUR - Dewi Handriana N. Meo; I Nyoman Sudiarta; I Ketut Suwena (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2019)
Tourist Information Center (TIC) is a facility that provides specific information about local areas, tourist attractions, festivals and all services related to tourism in the area. The purpose of this study was to determine how much influence the Quality of Service and Trust Affected on Foreign Tourist Satisfaction Using the Tourist Information Center in Labuan Bajo East Nusa Tenggara. Determination of samples in this study using purposive sampling method as many as 115 respondents. Data collection techniques using questionnaires, observation, interviews, documentation, and literature. The data analysis technique in this study is descriptive analysis, validity and reliability, classic assumptions, multiple regression analysis, correlation analysis, and coefficient of determination analysis using SPSS version 17.0.The results of this study indicate the effect of service quality on the satisfaction of foreign tourists using the Tourist Information Center in Labuan Bajo was stated to have a very significant effect with a tcount of 5.243> t table 2.23214. The effect of trust on satisfaction shows a significant value of 8.924> t table 2.23214, while for the influence of service quality and trust simultaneously on satisfaction is significant with a value of 151.617> t table 1.770.